The European Union in the Coronavirus Crisis - ZG Überblick (Wirtschaftsdienst)
Abstract The Coronavirus crisis has affected al of thel member states in the European Union — but some earlier and harder than others. A large rescue package is to be set up, the financing, conditions and possible requirements of which are still being disputed by EU members. The levels at which the measures are to be organised have not yet been established either. What is the importance of the national level or the supranational leves? Is it primarily about the European Monetary Union or about the EU as a whole? Solidarity is not only required by the European idea, but also by economic necessity, since the member states are strongly connected by their supply chains.